Assessment & Intervention in Social Work : Preparing for Practice - Beckett, Chris (SAGE Publications, Ltd. (UK), 2010)
Chris Beckett′s new book on assessment and intervention in social work practice covers the core topics for qualifying social work students. The book provides a thorough understanding of the issues and skills essential for effective practice. Each of the nine chapters defines a key concept, including Assessment; Intervention; Risk and Efficacy. Case studies and ′practice questions′ throughout make the connections between theory and practice explicit. Suggestions as to further reading are made at the end of each chapter. This important book is essential reading for undergraduate and postgraduate social work students throughout all three years of their training, but it will be particularly useful for students who are on on placement, or who are reflecting on their experiences on placement. It is also a useful resource for practice teachers who need a framework for discussing practice with students they supervise on placement.